(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Hydrochlorides of 2,3-trimethylene-3,4-dihydroquinazoline (deoxypeganine, 3) and 2,3-trimethylene-3,4-dihydroquinazolin-4-one (deoxyvasicinone, 4), 2,3-trimethylene-3,4-dihydroquinazolin-4-thione (deoxyvasicinthione, 5), 2,3-tetramethylene-3,4-dihydroquinazolin-4-thione (mackinazolinthione, 7), 2,3-pentamethylene-3,4-dihydroquinazolin-4-thione (9) were synthesized and their insecticidal activity have been studied. It was found that compounds 3 and 4 have low cytotoxicity, but increasing of quantity of methylene groups in positions 2 and 3 in the series of the thio-analogues 5→7→9 leads to the increasing of cytotoxic activity of them. “Structure-activity” relationship among the tricyclic quinazoline-4-thiones (5, 7, 9) was revealed. It should be noted that the compounds, consisting reactive thiocarbonyl group are important starting substances for further investigations. The obtained results shows that six-membered and seven-membered quinazolin-4-thiones - 7 and 9 in concentration 1 µg/ml are inhibited cell growth by 59% and 65%, respectively compared with the control, indicating that these compounds can serve as a basis for the development of the new insecticides. Structure of the synthesized compounds was confirmed by the physical methods of research.